Are DSM and logic not on good terms?. (August 2015) - Dome, Peter; Demeter, Zoltan; Gonda, Xenia; Rihmer, Zoltan
Summary: We would like to draw attention to the fact that the recently published DSM-5 (and also its predecessor, DSM-IV) contains annoying errors that are mainly logical in nature. These mistakes are undoubtedly a result of inadvertence, rather than either conceptual (professional) disagreements between authors/editors or shortage of scientific data for appropriate circumscription of diagnostic categories. The good news is that since these errors are mainly logical ones, they can be recognised and repaired.